Conciencia ambiental y manejo de residuos sólidos en estudiantes de segundo grado de ciencias naturales en la institución educativa pública inicial primaria y secundaria de menores N° 60087 Lucille Gagne Pellerin Santa Clotilde río Napo 2021 - Napuche Lomas, Alejandra (2021)
The main objective of this study has been to relate the results of environmental awareness and solid waste management in Second Grade students in Natural Sciences at the Initial, Primary and Secondary Public Educational Institution for Minors No. 60087 Lucille Gagne Pellerin, Santa Clotilde Río Napo in 2021. As a methodology, the relational type of research has been taken, through a field, cross-sectional, and bivariate design. The population has been made up of 174 second-grade high school students and the sample was census, that is, 174 students. The survey has been used as a data collection technique and a questionnaire as an instrument, which has been validated by judges. The conclusion of the research is that between both variables there are 14.9% and 12.1% of the students with a lack of environmental awareness, they handle solid waste regularly and badly, respectively; Of the students with a low presence of environmental awareness, 35.6% and 8.0% show regular and good solid waste management respectively and in those who show a high presence of environmental awareness, 12.1% and 6.9% show management regular and good solid waste respectively.